Edge Finite Elements for 3D Electromagnetic Field Modeling - Tarvydas, P. (Elektronika ir Elektrotechnika, 2007)
Edge Finite Elements are analyzed, since they are gaining more and more popularity in modeling of electronic devices. Comparison of Edge Finite Elements and Nodal Finite Elements is presented, their advantages and lacks are introduced, also recommendations for their application are given. Form functions used to describe rectangular finite element in 3D space are presented. Possibilities of the various finite element analysis software packages are analyzed. Properties of the edge finite element SOLID117, which is implemented in the software package ANSYS/Emag and intended for modeling of low-frequency electromagnetic fields, are discussed here. Generalized electromagnetic field modeling algorithm using edge finite elements was created. Il. 5, bibl. 7 (in English; summaries in English, Russian and Lithuanian).